2019
DOI: 10.1021/acs.jproteome.9b00487
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Proteomic Characterization of Truncated Proteoforms

Abstract: A top-down proteomic strategy with semi-automated analysis of data sets has proven successful for global identification of truncated proteins without the use of chemical derivatization, enzymatic manipulation, immunoprecipitation or other enrichment. This approach provides the reliable identification of internal polypeptides formed from precursor gene products by proteolytic cleavage of both the N-and C-termini, as well as truncated proteoforms that retain one or the other termini. The strategy has been evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…In this study, proteoforms were considered identified when the difference between observed and theoretical masses was ≤10 ppm and P-Score was ≤1 × 10 –04 . , While an “absolute mass search” on ProsightPD limits the search space to species matching the precursor mass, a “biomarker search” expands the search space to fragments of protein sequences that match the precursor mass. In this study, the majority of the proteoforms (>70%) were identified by the biomarker search, which indicates the presence of several truncated proteoforms . In addition to strong evidence of protein identification, concordance between theoretical and observed masses of precursor ions is a significant advance to a successful proteoform identification.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…In this study, proteoforms were considered identified when the difference between observed and theoretical masses was ≤10 ppm and P-Score was ≤1 × 10 –04 . , While an “absolute mass search” on ProsightPD limits the search space to species matching the precursor mass, a “biomarker search” expands the search space to fragments of protein sequences that match the precursor mass. In this study, the majority of the proteoforms (>70%) were identified by the biomarker search, which indicates the presence of several truncated proteoforms . In addition to strong evidence of protein identification, concordance between theoretical and observed masses of precursor ions is a significant advance to a successful proteoform identification.…”
Section: Resultsmentioning
confidence: 56%
“…In this study, the majority of the proteoforms (>70%) were identified by the biomarker search, which indicates the presence of several truncated proteoforms. 32 In addition to strong evidence of protein identification, concordance between theoretical and observed masses of precursor ions is a significant advance to a successful proteoform identification. For instance, the mass difference between arginine and citrulline is +0.984 Da and between lysine and allysine is −1.0316 Da.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another advantage of using SPE-based extraction is that proteins contained in the aerosol particles can be preserved. Mass spectrometry-based rapid identification of proteins without enrichment and enzymatic digestion were developed 37 . As a result, signature proteins characterized by TB patients could be combined with lipid biomarkers to provide a more reliable diagnostic approach for the identification of active TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Monoisotopic masses were deconvoluted using Xcalibur software 3.0 (Thermo Fisher Scientific) and the fragmentation ions were interpreted using ProSight Lite (northwestern.edu). 20,21 For richer details on top-down mass spectrometric data analysis, the reader may refer to our previous studies and the supplemental information. Figure 1.…”
Section: Methodsmentioning
confidence: 99%